BASIC PROFESSIONAL COMPETENCIES OF STUDENTS OF «INFORMATION, LIBRARY AND ARCHIVAL SCIENCE» IN DNEPROPETROVSK COLLEGE OF CULTURE AND ARTS - Khoroshylova, Nadiya S. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The components of the professional competence of librarians are considered; ways of their formation during training in Dnepropetrovsk College of Culture and Arts are shown.